The Oral History of Photographs: Collaboration, Multi-Level Engagement, and Insights from the Adrian Paton Collection - Harkema, Craig; Carlson, Keith (KULA, 2018)
This paper outlines notable features of the Adrian Paton Photo and Oral History Collection at the Saskatchewan History & Folklore Society (SHFS) and discusses aspects of the relationships formed between the local collector, faculty at the University of Saskatchewan, the SHFS, and members of the community-based cultural heritage digitization project during the collection’s creation and curation. We also outline the benefits and challenges for university-led digital projects that seek to partner with a wide range of participants, with a focus on community members, local organizations, and students enrolled in programs at their institution. Additionally, we discuss the transformative potential of such partnerships for academic institutions and what to consider when entering into collaborations of this nature.